Dynamic verification of satellite systems using Ilities. Issue 2 (June 2022) - Brown, Mason; Dey, Sharmistha; Tuxworth, Gervase; Bernus, Peter; de Souza, Paulo
ABSTRACT: The research outlines the design for an 'ilities tool' to assist small satellite verification. Prior literature commonly requests for ilities to be built-in to small satellite systems to prevent failure. Test standards are reviewed to define critical ilities. Definitions are then used to develop calculations that system designers can automate with a software tool. Previous failure data are used to predict the reliability of a future small satellite system. Bayesian estimation is applied to a qualitative NASA database of 219 small satellite (0.001–180 kg) failures from 2000 to 2016 to generate eight failure categories. A communication system (47%) or the attitude control (16%) failure are most likely to occur. A failure in the communication system has a low chance of survivability (16%). A failure within the attitude control system is expected to end with partial mission success (54%). The research suggests that an ilities tool can contribute to dynamically aiding verification. Such a tool will complement small satellite verification methods currently described by testing standards.